Interorganizational knowledge sharing in a science and technology park: the use of knowledge sharing mechanisms. Issue 10 (25th April 2019) - Balle, Andrea Raymundo; Steffen, Mário Oscar; Curado, Carla; Oliveira, Mírian
Abstract : Purpose: This paper aims to uncover the combinations of knowledge sharing mechanisms that organizations in a science and technology park in Brazil use to share managerial and technical knowledge. Design/methodology/approach: This research adopts a qualitative approach that uses a fuzzy set qualitative comparative analysis to analyze data that are gathered from 51 managers of organizations in a science and technology park. Findings: The results show that knowledge sharing happens regardless of the type of knowledge. There are more alternative paths that lead to knowledge sharing than to its absence. Regarding the type of knowledge shared, there are more alternative configurations that lead to managerial knowledge sharing than to technical knowledge sharing. Only the older organizations in the science and technology park abstain from knowledge sharing. Research limitations/implications: Due to the qualitative nature of the study, no generalization is possible. Additionally, the study's limitation is that it involves organizations from a single science and technology park. Practical implications: The results offer managers of organizations in science and technology parks to choose from alternative combinations of mechanisms to either boost their knowledge sharing or to promote knowledge protection. Originality/value: The paper provides an original contribution by identifying the combinations of mechanisms that organizations in a science and technology park use that leads to the sharing of specific knowledge types. The findings also identify the combination of mechanisms that older organizations use that prevents them from sharing knowledge.